Analysis of Factors Influences Fraudulent Tendencies in Denpasar Rural Credit Institutions - Ida Ayu Budhananda Munidewi; Ni Nyoman Ayu Suryandari; I Made Suryawan (International Journal of Applied Business and International Management, 2019)
Accounting fraud often occurs and increases in several countries and organizations. The deviant action in financial statements is one of the accounting fraudulent actions. The impact and consequences of accounting fraud cannot be avoided and microfinance institution will suffer losses due to this action. This study aims to examine and obtain empirical evidence of the effectivity of internal control effectiveness, information asymmetry, compliance with accounting rules and management morality towards accounting fraudulent tendencies in Rural Credit Institutions (LPD) in Denpasar City. Data is obtained by giving questionnaires to the leadership and accounting staff at the Rural Credit Institution (LPD) in Denpasar City. Determination of the sample using purposive sampling method. The sample in this study were 70 respondents. The analytical tool used is multiple linear regression analysis. The data obtained were analyzed using the Statistical Package for Science (SPSS) program. The results showed that the effectiveness of internal control and management morality had a negative effect on accounting fraud tendencies. While information asymmetry and compliance with accounting rules do not affect the tendency of accounting fraud.